One cheer for Constantinople: A comment on Pettit and Skinner on Hobbes and freedom - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 2009)
Philip Pettit and Quentin Skinner find Hobbes's understanding of freedom as non-interference inadequate because it fails to appreciate what is wrong with a life lived as a slave. Though their critiques have some force, however, Hobbes's view of freedom has virtues of its own. It is highly sensitive to the fact that freedom is a matter of degree. It is also unlikely to mistake freedom for something else, like security or dignity. Moreover, Hobbes is not as unmindful of the dangers of servility as many think.